2002
DOI: 10.1016/s0885-3924(02)00487-6
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Observation of Corticosteroid Use at the End of Life in a Hospice

Abstract: This study aimed to clarify corticosteroid prescribing during final hospice care, realizing the clinical and ethical dilemmas that may be associated with this therapy. A retrospective review was performed of deaths occurring at our unit during a 6-month period. Corticosteroid use was recorded from drug charts and cross-referenced by case note review. Fifty-one percent of 178 patients received corticosteroids, which were continued until death in 53%. Only 2% were switched from oral to parenteral corticosteroids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 8 publications
3
35
0
4
Order By: Relevance
“…Two-thirds of the physicians treating patients with advanced cancer claimed that they prescribed corticosteroids to more than 50% of their patients, and 52% of the cancer patients were actually treated. The proportion of patients on corticosteroids in this study is in accordance with earlier studies from other countries [8,9,11] and reflects the wide range of indications for this treatment. The finding that almost 70% of the patients in in-patient units had ongoing treatment with corticosteroids raises the question on whether the use of these potent drugs has become a matter of routine rather than a closely monitored specific treatment.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Two-thirds of the physicians treating patients with advanced cancer claimed that they prescribed corticosteroids to more than 50% of their patients, and 52% of the cancer patients were actually treated. The proportion of patients on corticosteroids in this study is in accordance with earlier studies from other countries [8,9,11] and reflects the wide range of indications for this treatment. The finding that almost 70% of the patients in in-patient units had ongoing treatment with corticosteroids raises the question on whether the use of these potent drugs has become a matter of routine rather than a closely monitored specific treatment.…”
Section: Discussionsupporting
confidence: 91%
“…Few physicians had local guidelines on treatment with corticosteroids in advanced cancer. Earlier studies have stressed the need for guidelines, and given the frequency of use and the potentially serious adverse side effects associated with corticosteroid treatment, implementation of guidelines are important [6,7,11]. The results in both surveys were coherent regarding the proportion of patients treated, drugs and dosages, assessed effects and side effects.…”
Section: Discussionmentioning
confidence: 80%
“…5,7,8 The physicians were first asked to report their rate of agreement regarding corticosteroid therapy using a non-Likert-type scale and to report on their actual clinical experiences regarding corticosteroid treatment of adult cancer patients with an estimated survival of 6 months or less who were not on anticancer treatment. The questions focused on corticosteroid therapy for the specific symptoms of anorexia, fatigue, and dyspnea, which were the most common indications for steroid therapy reported in the literature, because we speculated that the physicians' attitudes might differ for each of these symptoms.…”
Section: Questionnairementioning
confidence: 99%
“…The questions focused on corticosteroid therapy for the specific symptoms of anorexia, fatigue, and dyspnea, which were the most common indications for steroid therapy reported in the literature, because we speculated that the physicians' attitudes might differ for each of these symptoms. 8,9 The questionnaire was divided into four sections.…”
Section: Questionnairementioning
confidence: 99%
“…The ethical dilemma that arises at this point is whether or not to continue dexamethasone parenterally, via the subcutaneous route, when the oral route is lost, in those patients who have been continued on corticosteroids throughout the end-of-life period. One retrospective study of corticosteroid-use in a specialist palliative care unit, which included brain tumour patients, focused specifically on the last few days of life and showed that only 2% (n = 90) of patients receiving long-term corticosteroids in the terminal phase of life were switched to parenteral corticosteroids when the oral route was lost [60]. This indicates that corticosteroids are withdrawn abruptly in the last few days of life in the majority of cases.…”
Section: Prescribing In the Terminal Phasementioning
confidence: 99%